DEVELOPMENT OF LOW-POLY VISUALIZATION-BASED AUGMENTED REALITY FOR POWER SUPPLY CIRCUIT LEARNING AT SMK N 2 PAYAKUMBUH - Mizan Malik; Titi Sriwahyuni; Rido Putra; Mahesi Agni Zaus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Difficulty in visualizing the operational processes of power supply circuits remains a challenge in electronics education at Vocational High Schools (SMK), particularly regarding abstract and dynamic concepts such as rectifiers and voltage filters. The use of two-dimensional media combined with verbal explanations makes it difficult for students to understand the relationships between components and the overall workflow of the system. This design aims to develop Augmented Reality (AR)-based learning media using a low-poly visualization approach through the Assemblr Edu platform, focusing on power supply circuit material for 11th-grade students in the Audio-Video Engineering Department at SMKN 2 Payakumbuh. The low-poly approach is used to simplify visual representations, thereby reducing display complexity without neglecting the functional characteristics of electronic components. This study adopts the Multimedia Development Life Cycle (MDLC) method, which includes the concept, design, material collection, assembly, testing, and distribution stages. The result of this development is an interactive AR platform that displays 3D objects, animations of circuit operations, instructional videos, and interactive assessments. The platform was designed to support a more concrete and interactive visualization of circuit operations in electronics education at vocational high schools.